Identification of Polysaccharides From Dipsacus asperoides and Their Effects on Osteoblast Proliferation and Differentiation in a High-Glucose Environment - Xu, Duoduo; Liu, Jia; Zheng, Wei; Gao, Qipin; Gao, Yang; Leng, Xiangyang (Frontiers in Pharmacology, 2022)
Polysaccharides (DAI-1 and DAI-2) from Dipsacus asperoides (D. asperoides) were obtained using mixed-bed ion exchange resin and Sephadex G-50 column chromatography following which their properties, structures, and activities were investigated. The results showed that DAI-1 and DAI-2 were homogeneous in nature, with glucose the only constituent, and had molecular masses of 17 and 4 kDa, respectively. Methylation analysis indicated that the backbones of DAI-1 and DAI-2 were mainly composed of (1→6)-linked glucose residues. DAI-1 possessed a small number of side chains and a branch point of (1→3, 6)-glucose, while DAI-2 lacked branching. Activity assays demonstrated that exposing osteoblasts to different DAI-1 concentrations (25, 50, or 100 μg/mL) in a high-glucose environment induced cell proliferation and led to a significant increase in bone morphogenetic protein 2 (BMP-2) and runt-related transcription factor 2 (Runx2) expressions at both the mRNA and protein levels. Moreover, DAI-1 treatment significantly increased alkaline phosphatase (ALP) and osteocalcin (OCN) activities in osteoblasts. Combined, our results suggested that DAI-1 may promote osteoblast proliferation and differentiation in a high-glucose environment.